Genome-wide associations for benign prostatic hyperplasia reveal a genetic correlation with serum levels of PSA - Julius Gudmundsson (Nature Portfolio, 2018)
Elderly males are often affected by benign prostatic hyperplasia and associated lower urinary tract symptoms (BPH/LUTS), but their link to prostate cancer risk is not well defined. Here, a genome-wide association study of BPH/LUTS patients from Iceland and the UK found 23 significant variants at 14 loci, and 15 of these variants associate with prostate specific antigen, which is linked to prostate cancer risk.